ANALISIS PENGGUNAAN WORK PREPARATION SHEET DAN PERAN INSTRUKTUR TERHADAP KETRAMPILAN MEMBUAT ULIR SQUARE PADA MATA PELAJARAN PRAKTIK OPERASI MESIN BUBUT LANJUT SISWA SMK BHINEKA KARYA - Rosandi Surya Wijaya; Muhammad Akhyar; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The objectives of this study were: (1) correlation between Work Preparation Sheet (WPS) and threading skills in practicum on advanced machining practice subjects at Bhinneka Karya Surakarta Vocational School, (2) relationship between instructor role and threading skills in practical subjects of machining practice subjects continued at Bhinneka Karya Surakarta Vocational School, (3) relationship of WPS implementation between the instructor's role simultaneously and the skill of making square threads in practical subjects in advanced machining practice subjects at Bhinneka Karya Surakarta Vocational School. The population of this study was all students from class XI in the mechanical engineering program at Bhinneka Karya Surakarta Vocational High School. The Issac-Michael table of 84 students raised the sample size. The sample members are appointed using simple random sampling technique. This processing data uses IBM SPSS version 21.0 software. The results of this study indicate that the useful contribution given by the WPS variable to the skill of making square yarn is 43.9%, while variations in the role of the instructor create a valuable contribution of 12%. This shows that both variables contribute effectively to the skill of making square yarn by 55.9%, and there are 44.1% influenced by other factors not explained in this study. The implementation of WPS as a medium for practical learning and the instructor role as a facilitator's practice results in students' efficiency in turning machine practices into making square threads in terms of faster time processing and improved practice scores.